MODEL ANTESEDEN EMPIRIS YANG MEMPENGARUHI ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) - Pangemanan, Enjang Hening; Suharnomo, Suharnomo (Diponegoro Journal of Management, 2016)
This study aims to examine empirical antecedent model that influence Organizational Citizenship Behaviour (OCB) appereance of employees in hospital. Whereas antecedent variabels of OCB are Perceived Organizational Support, Leader-Member Exchange, and Impression Management. While the mediation variable is Felt Obligation. Objects of this study are nurses as employee, and room heads as supervisor in General Centre Hospital Dr.Kariadi Semarang. Sample  taken by random sampling technique to 120 respondents. This study were analyzed using Partial Least Square method in Warp PLS 4.0 software. An empirical antecedent model of OCB were accepted. Perceived Organizational Support (POS) variable and Leader-Member Exchange(LMX) variable  were proved positively significant influencing both toward OCB through mediation variable, Felt Obligation (FO), and  positively significant influencing independent variable, OCB. Thus variable Impression Management (IM) only well influencing  directly towards OCB, and not positively influence toward FO as mediation variable.